Aggregative games - Luis C. Corchón (SERIEs - Journal of the Spanish Economic Association, 2021)
This survey presents in a historical way the main contributions to the hardcore theory of aggregative games and the applications of this model to several fields of economics, other social sciences and engineering.
Keywords: C7; L1; L2; 330; Aggregative; Games; Quasi-competitiveness; Shocks